Pilot Safety and Feasibility Study of Non-invasive Limb Proprioceptive Cerebellar Stimulation for Epilepsy - Harper, Ronald M.; Hertling, Dieter; Curtis, Ashley; Sauerland, Eberhardt K.; De Giorgio, Christopher M. (Frontiers in Neurology, 2021)
Cerebellar stimulation reduces seizures in animals and in humans with drug-resistant epilepsy. In a pilot safety and feasibility study, we applied continuous cutaneous vibratory stimulation (limb proprioceptive cerebellar stimulation) to foot limb proprioceptive receptors to activate cerebellar, pontine, and thalamic structures in drug-resistant epilepsy patients for 8-h nocturnally up to 6-months after a 4-week pre-treatment control baseline. Seizure frequency was evaluated during the baseline control period, and at 6, 12, and 24 weeks after the control recordings. Five-subjects completed at least the first 6-week treatment. At 12-weeks, the median reduction in seizure frequency was −27.8% (mean reduction = −22.3%). Two subjects continued for 24 weeks, with a decline of −44.1 and −45.4%. This pilot study provides support for further clinical studies into the safety and efficacy of limb proprioceptive cerebellar stimulation for epilepsy.